Herpetiform dermatitis: A case report - Hazlianda, Cut Putri; Muslim, Medina (Journal of Pakistan Association of Dermatologists, 2024)
Herpetiform dermatitis (HD) also known as 'morbus duhring' is a chronic autoimmune skin disease that causes severe itching. This condition is associated with antitransglutaminase IgA autoantibody on the superficial papillary dermis layer that causes neutrophil infiltration and blister formation. Formerly, it was explained by American dermatologist, Louis Adolphus Duhring in 1884. This disease is characterized by papules, vesicles, plaques, urticaria, erythema, and excoriations that vary from 1–3 mm, mainly located on the extensor areas of the upper and lower extremities, shoulders, mid-back, and buttocks that are symmetrically distributed. HD is known to be associated with gluten-sensitive enteropathy (GSE) or celiac disease (CD) which is believed to play an important role in its pathogenesis. More than 90% of HD patients are shown to be gluten-sensitive. This case report investigates HD’s clinical characteristics and association with GSE or CD in a defined patient population.